Expression Patterns of Key Hormones Related to Pea (Pisum sativum L.) Embryo Physiological Maturity Shift in Response to Accelerated Growth Conditions - Ribalta, Federico M.; Pazos-Navarro, Maria; Edwards, Kylie; Ross, John J.; Croser, Janine S.; Ochatt, Sergio J. (Frontiers in Plant Science, 2019)
Protocols have been proposed for rapid generation turnover of temperate legumes under conditions optimized for day-length, temperature and light spectra. These conditions act to compress time to flowering and seed development across genotypes. In pea, we have previously demonstrated embryos do not efficiently germinate without exogenous hormones until physiological maturity is reached at 18 days after pollination (DAP). Sugar metabolism and moisture content have been implicated in the modulation of embryo maturity. However, the role of hormones in regulating seed development is poorly described in legumes. To address this gap, we characterized the hormonal profiles (IAA, 4Cl-IAA, GA20, GA1 and ABA) of developing seeds (10-22 DAP) from diverse pea genotypes grown under intensive conditions optimized for rapid generation turnover and compared them to profiles of equivalent samples from glasshouse conditions. Growing plants under intensive conditions altered the seed hormone content by advancing the auxin, GAs and ABA profiles by 4-8 days, compared with the glasshouse control. Additionally, we observed a compression of the auxin profiles across genotypes. Under intensive conditions, auxin peaks were observed at 10-12 DAP and GA20 peaks at 10-16 DAP, indicative of the end of embryo morphogenesis and initiation of seed desiccation. GA1 was only detected in seeds harvested in the glasshouse. These results were associated with an acceleration of embryo physiological maturity by up to four days in the intensive environment. We propose auxin and GA profiles as reliable indicators of seed maturation. The biological relevance of these hormonal fluctuations to the attainment of physiological maturity, in particular the role of ABA and GA, was investigated through the study of precocious in vitro germination of seeds 12-22 DAP, with and without exogenous hormones. The extent of sensitivity of developing seeds to exogenous ABA was strongly genotype-dependent. Concentrations between 5-10µM inhibited germination of seeds 18 DAP. Germination of seeds 12 DAP was enhanced 2.5-3 fold with the addition of 125µM GA3. This study provides further insights into the hormonal regulation of seed development and in vitro precocious germination in legumes and contributes to the design of efficient and reproducible biotechnological tools for rapid genetic gain.